Stability of a chemostat model of two microorganisms - Hossain, A B M Shahadat; Podder, Chandra Nath (BRAC University, 2010)
We studied stability analysis of a chemostat model of two microorganisms that incorporates both different response functions and we made a single code of the model using a computer algebra system (CAS) Mathematica for graphical illustration globally.